KREATIFITAS GURU PAI DALAM MENINGKATKAN MINAT BELAJAR DI KELAS X MADRASAH ALIYAH NEGERI 3 HULU SUNGAI TENGAH - Rahmad Hulbat (CV. ADIBA AISHA AMIRA, 2023)
The creativity of good PAI teachers is expected to increase students’ interest in learning in a better direction. Based on this statement, this research can be focused on the creativity of PAI teachers in increasing interest in learning at Tenth Grade of Madrasah Aliyah Negeri 3 Hulu Sungai Tengah and the purpose of this research is to find out the creativity of PAI teachers in increasing interest in learning at Tenth Grade of Madrasah Aliyah Negeri 3 Hulu Sungai Tengah. The subjects of this study are a PAI teacher and several students at Tenth Grade of Madrasah Aliyah Negeri 3 Hulu Sungai Tengah. While the object of this research is the creativity of PAI teachers in increasing interest in learning at Tenth Grade of Madrasah Aliyah Negeri 3 Hulu Sungai Tengah. Data collection techniques are carried out by means of observation, interviews, and documentation. Data processing techniques are carried out by data reduction, data display, and data verification. Data analysis techniques use qualitative and provide conclusions using general methods based on existing data in the field. The results of this study indicate that the creativity of PAI teachers in increasing interest in learning at Tenth Grade of Madrasah Aliyah Negeri 3 Hulu Sungai Tengah is reflected in PAI teachers always varying their learning, both by using various methods, using various media, changing seating arrangements - change, learning is sometimes in the classroom and sometimes outside the classroom. Each learning process is not monotonous or spelled out the same way, but always varies at each meeting. The results of the creativity of such PAI teachers make students’ enthusiasm in learning better and students' activeness in participating in learning is very visible. This is illustrated by the courage of students in asking questions, the courage of students in expressing their opinions in front of their friends and teachers. In addition, students are brave and don’t hesitate to appear in front of their friends and teachers to be an example in practicing or demonstrating the material being studied. This shows that students’ interest is very good in participating in learning in Islamic religious education subjects.